Effect of a fermented dietary supplement containing chromium and zinc on metabolic control in patients with type 2 diabetes: a randomized, placebo-controlled, double-blind cross-over study - Yu-Mi Lee; Petra Wolf; Hans Hauner; Thomas Skurk (Food & Nutrition Research, 2016)
Background: For the increasing development of type 2 diabetes dietary habits play an important role. In this regard, dietary supplements are of growing interest to influence the progression of this disease. Objective: The aim of this study was to investigate the effect of a cascade-fermented dietary supplement based on fruits, nuts, and vegetables fortified with chromium and zinc on metabolic control in patients with type 2 diabetes mellitus. Methods: This was a randomized, placebo-controlled, double-blind, intervention study under free-living conditions using a cross-over design. Thirty-six patients with type 2 diabetes mellitus were enrolled and randomized either to receive a cascade-fermented dietary supplement enriched with chromium (100 µg/d) and zinc (15 mg/d) or a placebo similar in taste but without supplements, over a period of 12 weeks. After a wash-out period of 12 weeks, the patients received the other test product. The main outcome variable was the levels of glycated hemoglobin (HbA1c). Other outcome variables were fasting blood glucose, fructosamine, and lipid parameters. Results: Thirty-one patients completed the study. HbA1c showed no relevant changes during both treatment periods, nor was there a relevant difference between the two treatments (HbA1c: p=0.48). The same results were found for fructosamine and fasting glucose (fructosamine: p=0.9; fasting glucose: p=0.31). In addition, there was no effect on lipid metabolism. Conclusion: This intervention study does not provide evidence that a cascade-fermented plant-based dietary supplement enriched with a combination of chromium and zinc improves glucose metabolism in patients with type 2 diabetes mellitus under free-living conditions.